The Influence of Tourist Facilities, Experiential Marketing and The Role of Tourism Ambassadors on Tourist Visiting Satisfaction - Wiska, Mayroza; Ermawati, Eka; Elida Putri, Dini; Ferdinal, Alex; Resty, Fenisi; Deswita, Yuhelvi (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of the study was to determine how much influence tourist facilities, experiential marketing and the role of tourism ambassadors on tourist visitor satisfaction of Alinia Farm &; Park Dharmasraya Regency in 2022. The method in this study is quantitative method and data collection using questionnaires assisted by SPSS version 20. Sampling in research is probability sampling which is a sampling technique that provides equal opportunities for each element (member) of the population to be selected as a member of the sample. The sampling technique used in this study is purposive sampling using accidental sampling method. Accidental sampling is a sampling technique based on chance. The population in this study was visitors to the Alinia Farm & Park tourist attraction, which was 73,142 visitors. The respondents sampled were 346 respondents. The results of the study showed that partially (t test) it was proven that tourist facilities had a positive and significant effect on visiting satisfaction with t value count > t table (5.633 > 1.966925), experiential marketing had a positive and significant effect on visit satisfaction with t value count > t table (4.659 > 1.966925) and the role of tourism ambassadors had a positive and significant effect on visiting satisfaction with t value calculate t > t table (6.398 > 1.966925) and simultaneously (test F) together with tourism facilities, experiential marketing and the role of tourism ambassadors have a significant effect on visit satisfaction with F value calculated > F table (79,443 > 2,398). The Adjusted R2 value is 0.406 which means that all independent variables can affect 40.6% of the dependent variable. The remaining 59.4% could be influenced by other factors not tested in the study.